A qualitative study of student attitudes, perceptions, beliefs, outlook and context in Qatar: Persistence in higher education - Batoul Khalifa (7004723) (2016)
This study attempts to address the challenges of students in higher education in Qatar. The study draws on student perceptions, beliefs, outlook, and context; we approach the study through grounded means by posing leading interview questions with the aim of exploring and probing. The approach is grounded in that no specific theory drives the questions; rather, the responses from the interview often require interpretation through theory to justify the findings. The sample comprised 35 students who were interviewed through probing and questioning techniques. The questions led to converging responses, which were segregated into themes. A large majority of students felt advising was absent or mismanaged, while some also were of the view that schools did not prepare them to enjoy the benefits of extracurricular activities; many students further viewed English or the Foundation Program (preparatory year's program) a barrier to their continuation in higher education. The most striking result was the apparent relationship between advising and student preparation in secondary school. Schools in Qatar and particularly independent schools (public schools) assign only a small role to advising and inducing strategies that reflect independence and any future anticipatory approaches to link expectations of higher education with support and guidance systems in secondary school. Other Information Published in: Near and Middle Eastern Journal of Research in Education, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/nmejre.2016.2